A Causal Evaluation on The Issue of Femicide: The Instinct of Possession - Kolburan, Şahide Güliz (The Bulletin of Legal Medicine, 2017)
Femicide that is an increasingly agenda in our country has been tried to be investigated through the fact of having. The perception of gender, femininity and masculinity is important in terms of determining the positions, roles and duties in community. In this study, “the sense of having” which is thought to have emerged from the perception of gender, has been tried to be explained by Fromm’s concepts of “to be” and “to have”. For this study scholarly articles, books and dissertations about femicide and its leading factors as well as statistical results of 2017 from “We Will Stop Femicide Platform” have been reviewed. Fromm’s concept of “to be” finds itself as “self-realization” in Humanistic/ Existentialist theories. Self-realization in humanistic theories defines a psychologically healthy person. Fromm defines “having” as to take possession, to dominate on it and to have right to use it. Since “having” brings with it its protection at any cost, the loss of possessed object is perceived as a threat to integrity of personality. Studies often show that men resort to violence when they perceive threats to their authorities or statutes. If the masculine authority is perceived as the basic element of the man’s self, the opposition is perceived totally as an attack to the self The perception of a woman as a possessed object brings with it the right to use her as he wishes and the right to kill her when necessary. It is important to have long-term and systematically planned “being” based trainings in.....